Psych. The complete third season [videorecording (DVD)] - Roday, James; Hill, Dulé; Omundson, Timothy; Bernsen, Corbin, 1954-; Lawson, Maggie; Nelson, Kirsten; James, Liam; Brocklebank, Sage (Psych (Television program), 2009)
Shawn Spencer pretends to be a psychic. No one really believes him, but he continues to be so helpful to the police that they keep calling him in on cases they can't solve. Shawn brings his childhood friend, Gus, into his scheme, and between their bantering they manage to solve every case they're presented with.